Recidivism among drug offenders: A survival analysis of the effects of offender characteristics, type of offense, and two types of intervention - Hepburn, John R. (Journal of quantitative criminology, 1994)
The determinants of recidivism are increasingly becoming the focus of public concern. This study explores the relative effect of type of intervention, offender characteristics, and type of incident offense on time to a petition to revoke probation and time to a probation revocation. Our analysis of intervention effects includes both parametric and nonparametric estimation procedures. Estimating five distributional forms of survival and a proportional hazard model for each measure of recidivism, the analysis indicates no difference in the effect of a program of drug monitoring and treatment, compared to drug monitoring only, for either of the two measures of recidivism. In addition, findings indicate that younger offenders and African American offenders have a shorter time to a petition to revoke probation. We also found a reduced time to failure for a probation revocation for African American offenders and offenders with a prior arrest record. Our findings offer empirical support for a reconsideration of the type of intervention effective in deterring offenders while on probation.